PENGARUH POPULARITAS TERHADAP PENINGKATAN PARTISIPASI PEMILIH PEMULA PADA PILEG 2019 (Studi pada popularitas eko patrio di daerah pemilihan DKI Jakarta 1) - Andi Yusuf Fadhilah (2023)
This study aims to discuss the influence of popularity on the increase in first-time voters in East Jakarta. By using the theory of political participation put forward by Huntington. In this study, we measure how the influence of celebrity popularity has on the interest of first-time voters in politics. The method used in this research is descriptive quantitative using primary data and secondary data. The sampling technique in this study used a non-probability quota sampling technique by first classifying prospective respondents before filling out the research data questionnaire. The data collection method used was a survey by sending an online questionnaire in the form of a Google form to samples domiciled in East Jakarta with an age interval of 17 to 21 years during the 2019 election. Researchers used six stages of data analysis, namely data collection, data editing, data coding. , data processing, cleaning data and data processing. The final results of this study indicate that there is an increase in the interest of first-time voters towards the popularity of celebrities who enter the world of politics. There is an influence between the popularity of celebrities on the interest of first-time voters when they vote in elections. This is because a public figure is a figure they have at least seen, although most firsttime voters do not know the celebrity's performance in the political sphere, therefore this becomes a trigger for novice voters to prefer celebrities compared to other candidates they have never seen before. know beforehand. The trick of using celebrities to attract voters is still a relevant way today. Popularity is still a very important thing in the world of politics, because popularity can open up more information networks and coverage. This is also assisted by the existence of social media and mass media which make popularity have an important role. It can be concluded that the exposure possessed by celebrities is still an important factor in attracting votes in elections. Keywords: Popularity, elections, first time voters.